RESULTS OF AN INNOVATIVE ENTREPRENEURSHIP POLICY INSTRUMENT IN THE FEDERAL NETWORK OF PROFESSIONAL, SCIENTIFIC, AND TECHNOLOGICAL EDUCATION - do Carmo, João Paulo; Gusmao, Ariana Oliveira; Brotto, Humberto Henrique Ramos; Potin, Gabriel Adolfo Gomes; Martins, Filipe Barbosa (Seven Editora, 2026)
Considering the need to strengthen innovation and entrepreneurship within public education institutions, this research analyzes the outcomes of the Innovative Entrepreneurship (IE) project, an initiative of the Ministério da Educação (MEC) - Brazilian Ministry of Educationaimed, at the Rede Federal de Educação Profissional, Científica e Tecnológica (RFEPCT) - Federal Network of Professional, Scientific, and Technological Education. The study aims to evaluate the project’s impacts on the consolidation of entrepreneurial culture, research infrastructure, and institutional capacity for innovation generation and dissemination. To this end, a qualitative and quantitative methodological approach was adopted, based on the analysis of secondary data, surveys, and interviews with institutional actors involved in the project’s implementation. Thus, the findings indicate that the IE project significantly contributed to improving research conditions, expanding access to applied knowledge, and strengthening entrepreneurial practices within academic environments. However, challenges related to startup creation and innovation commercialization persist. This allows the conclusion that fostering innovative entrepreneurship in developing economies requires integrated public policies that align capacity building, technological innovation, and sustainable growth strategies to unlock long-term entrepreneurial potential.DOI: https://doi.org/10.56238/sevened2026.008-023